P501 Thiopurine withdrawal in patients with Crohn's disease: the SURESTE study. (15th January 2020) - Sánchez Rodríguez, E; Sánchez Aldehuelo, R; Guardiola, J; Gutiérrez Casbas, A; Domènech, E; Bermejo, F; Van-Domselaar, M; Mesonero Gismero, F; Suris, G; Muñoz Perez, R; Mañosa, M; Jiménez Márquez, L; et al.
Abstract: Background: Thiopurine (TP) withdrawal in patients with Crohn's disease (CD) in clinical remission (CR) is controversial. Our aim was to describe the evolution of CD patients in CR who discontinued TP prescribed to maintain a remission previously achieved with medical treatment, and to detect predictors of reactivation after withdrawal. Methods: Multicentric observational retrospective study including CD patients in RC under TP treatment, who electively discontinued TP. Relapse was defined as the need to start any specific treatment for CD, including surgery. Informed consent was obtained from the inclusion in the Eneida database. Results: We included 78 patients (52.6% females, age 45(19–77) years) of whom 57 presented an inflammatory, 12 a stricturing and 9 a penetrating behaviour; 31 patients had terminal ileum involvement, 9 colonic, 36 ilecolonic, and 2 ileocolonic plus upper gastrointestinal involvement, whilst 17 also had perianal disease. Mean disease duration was 13.47 (3.02–35.02) years. 48.7% had never smoked whilst 24.4% were active smokers. TP was started to maintain remission previously achieved with medical therapies in 78 patients (100%). Median azathioprine dose was 2.11 (1.3–2.6) mg/kg/d, and of 6-mercaptopurine (6MP) 1.44 (1–2) mg/kg/day. The median duration of TP treatment was 52.79 (3–268) months and of steroid-free remission 49.41 (1–177) months. Reasons for TP withdrawal were: patient choice/request in 20 (25.6%), physician proposal in 28 (25.7%), drug-related adverse events in 19 (24.4%) and miscellaneous in 11 (14.1%). By the time of TP discontinuation, median CRP was 5.08 mg/l (0.1–157.9), fecal calprotectin(FC) 282.38 µg/g (2.4-4430) and a mean 0.45 (0–4) in Harvey–Bradshaw Index (HBI); those who relapsed presented median CRP of 15.31 mg/l (0.1–125.31), fecal calprotectin (FC) 462.22 µg/g (90–1240) and a mean 5.46 (0–15) in HBI. These differences were statistically significant. During a 5.08 (0.12–13.05) years follow-up, 38 (48.1%) patients relapsed, with treatment duration being the only factor associated to risk of relapse (O r = 0.659 IC95 0.43–0.98, p = 0.04) in the multivariant analysis (IMAGE1). Conclusion: Thiopurine withdrawal in the context of sustained remission in CD is associated with relapse in almost half of the patients after a median follow-up of 5 years. Thiopurine treatment duration of shorter than 5 years was shown to carry greater risk for relapse.